Compliment Responses in English Made by Seventh Grade Students of SMPN 8 Sekayu - Gusmuliana, Paidi; Apriani, Eka; Supardan, Dadan; Syafryadin, Syafryadin; Suhermanto, Hadi (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2020)
This paper showed the compliment responses in English made by 7th grade students at SMP Negeri 8 Sekayu. The sample of this study was five females and five males of the 7th grade students. From the seven categories of compliment responses, there were only six compliment responses in English made by students: acceptance, positive elaboration, neutral elaboration, denial, smiling, and no response. The result of this study showed that: 1) female had highest percentage in positive elaboration and smiling; 2) male had highest percentage in denial and no response; and 3) female and male had same percentage in acceptance and neutral elaboration response. There was no negative elaboration response used by students (female and male). Hence, it can be said that students gender hold important effect in giving compliment responses in English.